Spatial Distribution and Diversity of Benthic Macrofauna in Coastal Waters of the Jabal Ali Marine Sanctuary (JAMS), Dubai - Jeruel Aguhob; Waleed Hamza; Andreas Reul; Muna Musabih; Jhonnel P. Villegas; Maria Muñoz (Diversity)
The present study aimed to characterize the benthic macroinvertebrate community of the Jabal Ali Marine Sanctuary (JAMS), the sole marine protected area in the Emirate of Dubai, during the summer and winter seasons of 2017. Limited research on the biological quality of the JAMS prompted this investigation, which involved 10 sampling stations to assess macroinvertebrate diversity and community composition in relation to abiotic factors such as sediment granulometry, trace metals, salinity, and temperature. Collected sediment samples were analyzed for macroinfauna, and their abundance was measured, revealing an average abundance of 2150 ind/m2 in summer and 2132 ind/m2 in winter without a significant difference between both seasons. Univariate indices, including the Margalef diversity index and Pielou evenness index, indicate a range of diversity values across sampling sites. Community composition was assessed through SIMPROF and Bray–Curtis similarity clustering, further elucidating the relationship between community structures and environmental gradients. The dominant macroinvertebrate species varied across seasons and stations, providing insights into seasonal variations in community dynamics. These findings contribute to the understanding of benthic community structures and biodiversity in the JAMS and serve as a baseline for future monitoring and management efforts aimed at preserving the ecological integrity of this important marine sanctuary.